Research on professional responsibility and ethics in accounting. 26 - Shawver, Tara J. (Emerald Publishing Limited, 2024)
This 26th edition of Research on Professional Responsibility and Ethics in Accounting explores many aspects across professional responsibility and ethics in accounting, including changing auditing approaches, whistleblowing, fraudulent practices, the impact of communications, and the impact Covid-19 has had on corporate social responsibility.
Keywords: Accounting -- Moral and ethical aspects.; Accountants -- Moral and ethical aspects.; Social responsibility of business.; Business & Economics -- Accounting -- General.; Accounting.; elektronické knihy; electronic books